Synthesis of self-supported non-precious metal catalysts for oxygen reduction reaction with preserved nanostructures from the polyaniline nanofiber precursor - Hu, Yang; Zhao, Xiao; Huang, Yunjie; Li, Qingfeng; Bjerrum, Niels J.; Liu, Changpeng; Xing, Wei (Journal of power sources, 2013)
Non-precious metal catalysts (NPMCs) for the oxygen reduction reaction (ORR) are an active subject of recent research on proton exchange membrane fuel cells. In this study, we report a new approach to preparation of self-supported and nano-structured NPMCs using pre-prepared polyaniline (PANI) nanofibers as both nitrogen and carbon precursors. The synthesized NPMCs possess nanoworm structures preserved from the PANI precursor and exhibit high onset potential of 0.905 V vs. RHE and selective activity of nearly four-electron ORR pathways. A significant enhancement in the intrinsic activity and onset potential for the ORR is observed when the Fe content in the precursor is increased from 0 to 3.0 wt.%, while further addition to 10.0 wt.% results in a decrease in the catalytic activity. ► Novel preparation of self-supported and nano-structured NPMCs for ORR. ► An onset potential of 0.905 V vs. RHE and nearly four-electron ORR pathway. ► Effects of ferrous species in precursors on the final catalysts explored. ► Onset ORR potentials increasing with the initial Fe content from 0 to 3.0 wt.%.